Creating of a remote-presence robot based on the development board Texas Instruments to monitor the status of infected patients - Chekubasheva, V. A.; Kravchuk, O. A.; Hlukhova, H.; Glukhov, O. V. (My University, 2022)
Statistics show that many infections of employees in medical institutions are associated with direct contact with patients. Furthermore, the deterioration of the patient’s condition in the intervals between doctor’s rounds was observed. Therefore, control and reduction of morbidity through introducing new monitoring methods without the direct involvement of human resources remains an urgent issue. This paper considers an alternative method for monitoring the state of infectious patients undergoing treatment. In this article, we have described the use of standard elements for scanning the medical state of people for the timely detection of pathologies with the implementation of instant notification of the attending physician. Based on the functionality of the Texas Instruments Robotics System Kit (TI-RLSK) developer board and additional sensors, an autonomous robot scanner was created. The considered embodiment of the model systemizes the provided recording recognition of a specific patient with the parameters of the health state in a database. In addition, the navigating system with an updated real-time map of the area enables the robot to deliver medicine to patients.
Keywords: Automated system; SLAM; Infrared sensor; Robot TI-RSLK; COVID-19